Atividade biológica de metabólitos secundários de Buddleja brasiliensis e Artemisia verlotorum - Gitzel Filho, Augusto (2011)
The present work describes the phytochemical study and biological activity evaluation of the Buddleja brasiliensis Jacq. ex. Spreng and Artemisia verlotorum Lamotte. Were isolated three compounds from Buddleja brasiliensis: verbascoside (1), β-sitosterol (54) and stigmasterol (55), and it was carried out a phytochemical screening, a study of the ability to inhibit the enzymes prolyl oligopeptidase (POP), dipeptidyl peptidase (DPP IV) and acetylcholinesterase (AChE), a study of the antimicrobial activity of the specie and the extraction of the essential oil. The fractions F4 and F12 inhibited significantly POP and AchE activity. All Buddleja brasiliensis fractions tested presented low activity of DPP IV inhibition. The phenylpropanoid verbascoside (1) demonstrated a significant and selective inhibitory activity against POP (IC50 = 1.3 mM), showed weak activity against DPP-IV (IC50 >> 150 mM) and was inactive against AChE (pMIQ 9.6). The essential oil obtained from this species has as major constituents the a-tujaplicin monoterpene (11.5%) and the diterpenoid heneicosane (14.5%). This oil was inactive against all tested enzymes. The antimicrobial activity of 1, the crude extract and fractions of Buddleja brasiliensis were tested against several fungi and bacteria. Fractions dichloromethane and ethyl acetate showed moderate activity against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae, Bacillus subtilis, Streptococcus pyogenes, while 1 showed no antimicrobial activity. The crude extract, fractions and essential oil obtained from Artemisia verlotorum were also evaluated for inhibitory activity against the POP and DPP IV, as well as against various fungi and bacteria. Dichloromethane fraction of Artemisia verlotorum showed the best antimicrobial activity, mainly against the yeast Saccharomyces cerevisiae, with an MIC of 125 μg/mL. Analysis by gas chromatography coupled with mass spectrometry of the essential oil of Artemisia verlotorum indicated as the main components santonilil acetate (37.2%) and a-cadinol (9.59%).